Isolation of Flavonoid Compound from Kareumbi Fruit (Homalanthus populneus (Geiseler) Pax) - Lamek Marpaung; Ronal Simbolon (Talenta Publisher, 2024)
Flavonoid compounds were isolated from Kareumbi fruit (Homalanthus populneus) using a sequential extraction and purification process. Methanol-concentrated extract was partitioned with ethyl acetate and n-hexane. The concentrated methanol extract was separated by column chromatography using a gradient elution of chloroform and methanol, varying the ratio 90:10; 80:20; 70:30; and 60:40 (v/v). Subsequent column chromatography yielded a yellowish-orange paste (19.6 mg, Rf = 0.73) from the chloroform:methanol (70:30) fraction. UV-visible, FT-IR, and 1H-NMR spectroscopic analysis confirmed that the isolated compounds belonged to the flavonol class of flavonoids.